Measuring Uranium in the Soil of Some Area in Missan Governorate/ Iraq - Baghdad Science Journal (Baghdad Science Journal, 2011)
Concentrations of uranium were measured in this study for twenty soil samples from four areas with different depths (soil surface-20-40-60-80)cm .The study regions include Missan Governorate (Al-Iskan area,Al-Shibbana area ,Hai-Al Moualimin Al Jadied area ,Sector 30 area). The Uranium concentrations in soil samples measured by using fission tracks registration in (CR-39) track detector that caused by the bombardment of (U-283) with thermal neutrons from (241Am-Be) neutron source that has flux neutron thermal of (5 ×103 n cm-2 s-1). The concentrations values were calculated by a comparison with standard samples. Through out the result, it was found that averages of uranium concentrations in soil samples were as the following : Al - Iskan area (0.404 ± 2.765) ppm, Al - Shibbana area (0.432 ± 1.719) ppm, Hai - Al - Moualimin Al - Jadied (0.236 ± 2.320) ppm, Sector 30 area (2.158±0.631) ppm.